Implementation Curriculum Integrative Education at Al-Khoirot Islamic Boarding School : Synergy Between Islam and Contemporary Era Competence - Vina Lailatul Maskuro; Ali Mukhammad Abrori (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
Study This driven by the crisis epistemological consequence dichotomy Islamic education that separates between religious knowledge and modern science. Objectives main study This is For analyzing the Pondok strategy Al- Khoirot Islamic Boarding School in balance mastery tafaqquh fiddin with development competence contemporary, as well as mechanism implementation synergistic curriculum mark Islam with demands 21st century. The methods applied is approach qualitative with design studies case, where data is collected through observation participatory, interview in-depth, and study documentation that is then tested through technique triangulation. Research results show that Al- Khoirot implementing an integrative curriculum model systemic through system dual (dual system) which requires all over students go through formal and religious paths in a way simultaneous. Findings key show existence acceleration yellow book teaching level high on the ladder medium, use literature bilingual jurisprudence (Arabic-English), as well as establishment of the English Club as laboratory Language daily. This strategy succeed synergize depth tradition the Salaf with global competence through synchronization tight schedule and management centralized education.